DEFENSE GEOGRAPHY AND THE CHARACTER OF THE INDONESIAN TOTAL DEFENSE SYSTEM (SISHANTA) - Susdarwono, Endro Tri (Universitas Negeri Surabaya, 2020)
Defense geography is a scientific study which is a branch of human geography. Starting from the implementation of military tactics, when reading topographic maps up to the implementation of military campaigns on a certain surface of the earth, so that how to determine and decide on defense policies and strategies always requires consideration of defense geography. In accordance with the defense system adopted by the Indonesian nation total defense system (Sishanta), namely a defense system mobilizes all national resources, both artificial resources and natural resources. That natural resources and space are geography or terrain to be used as much as possible to carry out total defense system (sishanta), in order to face threats, both of within and abroad. Introduction to defense geography, preferably in line with the preparation of the Defense Area Spatial Plan. Linkages between total defense system (sishanta) and Indonesia's geographic environment into consideration the urgency of the inclusion of defense geography in geography education in Indonesia.